1998
DOI: 10.1021/tx970156l
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Formation of 8-Hydroxy-2‘-deoxyguanosine and Single- and Double-Strand Breaks in DNA Mediated by Fenton Reactions

Abstract: The formation of 8-hydroxydeoxyguanosine (8-OHdG) and both single- and double-strand breaks in DNA by Fenton-type reactions has been investigated. Salmon sperm DNA was exposed to hydrogen peroxide (50 mM) and one of nine different transition-metal ions (25 microM-1 mM). Modified DNA was isolated and subjected to analysis by liquid chromatography coupled to an electrochemical detection system (LC-ECD), to evaluate the formation of 8-OHdG. The highest yield of 8-OHdG was obtained following treatment of DNA with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
2
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(92 citation statements)
references
References 36 publications
5
78
2
5
Order By: Relevance
“…2 Steady state levels of oxidatively generated damage are one or more orders of magnitude higher than those of non-oxidatively generated nucleobase adducts. 3 This result of so called "oxidatively generated stress" has been implicated in mutagenesis, disease 35 and aging. [4][5][6] One of the primary oxidatively generated stress biomarkers to have emerged in recent years is 8-oxoGua, a primary product of Guanine oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…2 Steady state levels of oxidatively generated damage are one or more orders of magnitude higher than those of non-oxidatively generated nucleobase adducts. 3 This result of so called "oxidatively generated stress" has been implicated in mutagenesis, disease 35 and aging. [4][5][6] One of the primary oxidatively generated stress biomarkers to have emerged in recent years is 8-oxoGua, a primary product of Guanine oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…A prime example is Hg(II) ion and Hg(II) compounds, which disrupt the hydrogen bonds between naturally occurring A-T base pairs and form T-Hg 2+ -T pairs (8,9). Redox-active metal ions are receiving much attention because of their ubiquitous presence in biological systems and their abilities to react with H 2 O 2 and other endogenous oxidizing agents to produce damaging reactive oxygen species (ROS), and an important topic in metal toxicity and carcinogenesis is metal-mediated oxidative DNA damage (10)(11)(12)(13) (15)(16)(17)(18). The suggested mechanism of oxidative DNA damage arising from Cu(II) involves a process in which Cu(II) is bound to a G-containing moiety in DNA and reduced to Cu(I) (16,(19)(20)(21).…”
Section: +mentioning
confidence: 99%
“…The structures of the mononucleoside 2′-deoxyguanosine (dG) and the accepted oxidative damage marker 8-OH-dG and its keto form 8-oxo-2′-deoxyguanosine (8-oxo-dG) are presented in Figure 2. The transition metal ions Fe(II), Cu(II), Cr(III), and V(III) produce significant levels of 8-OH-dG in the presence of H 2 O 2 (15), and the Cu(I)/H 2 O 2 system also yields significant 8-OH-dG levels (17). The reactive nature of radical species suggests that they are generated close to the site at which they react.…”
Section: Base Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvements in sperm motility, sperm DNA fragmentation, fertilization capacity, and odds of normal sperm count were observed in most studies [120][121][122][123], albeit, in a few of them, no advantage was documented [124,130]. A Cochrane metaanalysis on the use of oral antioxidants in male infertility found that these agents significantly improved pregnancy rates and live births and decreased sperm DNA damage [131].…”
Section: Prescription Of Antioxidantsmentioning
confidence: 99%